Experimental Analysis of Fluid Flow and Heat Transfer of Al2o3-Water Nanofluids in Turbulated Tube - Adhikari, Surya; Sah, Sudeep (Advances in Engineering and Technology: An International Journal, 2025)
Nanofluids have attracted huge attention due to their improved thermal properties. One prominent application of nanofluids is enhancing the thermal performance of heat exchangers. In this research work, experimental investigations were conducted to evaluate the effect of adding Al₂O₃-water nanofluids on the overall heat transfer coefficient in a shell and tube heat exchanger fitted with helical coil turbulators. Al₂O₃ nanoparticles were uniformly dispersed in water to create nanofluids with concentrations of 0.2% and 0.4% by weight. These nanofluids were used in the tube of the shell and tube heat exchanger having helical coil turbulators with pitches of 16 mm and 20 mm induced turbulence to enhance heat transfer. The study examined various parameters including nanofluid concentration and turbulator pitch, analyzing their effects on heat transfer and found that the use of Al₂O₃-water nanofluids leads to a significant enhancement of the thermal efficiency of the shell and tube heat exchanger. The maximum increase in the overall heat transfer coefficient was observed with 0.4% Al₂O₃-water nanofluid combined with a 16mm pitch helical coil.